Land-use change and human-elephant conflict in Sumatran Elephant Conservation - Ari Iswandari; Gopinda Fernandes; Ade Mudaha Putra; Reza Fitra Nanda; Suranto; Rahmawaty (Global Forest Journal., 2026)
This review aims to explore human-elephant conflict in the context of Sumatran elephant conservation, accounting for the impacts of land-use change and elephants' ability to move freely. The researchers used a method for identifying and selecting information from a large database, Scopus, which they accessed on May 16, 2026. They followed a series of steps to choose the studies, including checking document types and the content of the information, and arrived at 31 studies from different countries. They also used VOSviewer to visualize relationships among various topics. The main finding of this review is that human-elephant conflict is the most significant problem, and the key challenge is achieving peaceful coexistence. They saw that most of the information about this problem comes from India and China. There is not as much information from Indonesia and Sumatra. The review says the problem with Sumatran elephants is not that they raid crops, but how land is used and how the elephants can move. To help save the Sumatran elephants, it suggests people should use computer models to predict where problems will occur, study how the elephants move, and involve the local community in reporting problems and setting up warning systems.